2020
DOI: 10.3390/fib8120074
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Tests and Reliability Analysis of the Cracking Impact Resistance of UHPFRC

Abstract: Ultra-high performance (UHP) concrete is a special type of fibrous cementitious composite that is characterized by high strength and superior ductility, toughness, and durability. This research aimed to investigate the resistance of ultra-high performance fiber-reinforced concrete (UHPFRC) against repeated impacts. An adjusted repeated drop mass impact test was adopted to evaluate the impact performance of 72 UHPFRC disc specimens. The specimens were divided into six mixtures each of 12 discs. The only differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Previous studies that used steel fiber, polypropylene fiber and other synthetic fibers revealed a distinguished superiority of steel fibers, both in mono-fashion or when combined with synthetic fibers, where it could better improve the stiffness, tensile strength, flexural strength, ductility, shear strength and energy absorbance capacity [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], which totally supports the obtained results in this research. Scorza et al [ 44 ] tested different combinations of different length steel and polypropylene fibers and indicated that steel mono-fiber reinforced mixture retained the best fracture results and post-peak performance under mode I fracture test.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies that used steel fiber, polypropylene fiber and other synthetic fibers revealed a distinguished superiority of steel fibers, both in mono-fashion or when combined with synthetic fibers, where it could better improve the stiffness, tensile strength, flexural strength, ductility, shear strength and energy absorbance capacity [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], which totally supports the obtained results in this research. Scorza et al [ 44 ] tested different combinations of different length steel and polypropylene fibers and indicated that steel mono-fiber reinforced mixture retained the best fracture results and post-peak performance under mode I fracture test.…”
Section: Resultssupporting
confidence: 90%
“…As seen in Table 1 , several researchers revealed a significant COV from the drop-weight impact test. Drop-weight impact findings on various types of fibrous concrete clearly showed strong scattering in test results, which was consistent with previous research [ 45 , 53 , 55 , 56 , 58 , 66 , 67 , 68 ].…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…This phenomenon is due to the presence of fibre in concrete which distributes uniformly, restricting the macro crack formation, alleviating the concentration of stress. Consequently, changing the direction of cracks due to fibre-bridging action leads to delays in crack growth and failure [25,26]. In general, the percentage of SF in conventional fibrous concrete is restricted to 2% due to fibre balling, which creates poor fibre distribution and more internal flaws, leading to reduced compressing strength [27,28].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…This means that the enhancement in impact resistance of the fibrous mixtures is majorly due to incorporating steel fibres, with a percentage share of not less than 90% of the total percentage impact improvement. The use of steel fibres is widely proven to dramatically improve the fracture behaviour and impact resistance of concrete mixtures [25,39]. The smaller contribution of MWCNT was discussed in the previous paragraphs, while the limited contribution of GFM compared the total improvement in H1 and H2 can be attributed to: first, their localised function as only an intermediate barrier between the two layers, and second, to their lower strength compared to steel fibres.…”
Section: Cracking and Failure Impact Numbermentioning
confidence: 99%